The Accuracy of Ultrasound Volume Flow Measurements in the Complex Flow Setting of a Forearm Vascular Access. Issue 3 (July 2013) - Van Canneyt, Koen; Swillens, Abigail; Lovstakken, Lasse; Antiga, Luca; Verdonck, Pascal; Segers, Patrick
Purpose: Maturation of an arterio-venous fistula (AVF) frequently fails, with low post-operative fistula flow as a prognostic marker for this event. As pulsed wave Doppler (PWD) is commonly used to assess volume flow, we studied the accuracy of this measurement in the setting of a radio-cephalic AVF. Methods: As in-vivo validation of fistula flow measurements is cumbersome, we performed simulations, integrating computational fluid dynamics with an ultrasound (US) simulator. Flow in the arm was calculated, based on a patient-specific model of the arm vasculature pre and post AVF creation. Raw ultrasound signals were subsequently simulated, from which Doppler spectra were calculated in both a proximal and a distal location. Results: The velocity component in the direction of the PWD-US beam (vPWD ), in a centered, small, sample volume, can be captured accurately using PWD spectrum mean-tracking (maximum bias [mB] 8.1%). However, when deriving flow rate from these measurements, a high degree of inaccuracy occurs. First, the angle-correction of vPWD towards the velocity along the axis of the vessel is largely influenced by the radial velocity components in the complex flow field (mB=16.3%). Second, the largest error is introduced when transferring the centerline velocity to the cross-sectional mean velocity without any knowledge of the flow profile (mB=97.7%). Conclusions: In the setting of a forearm AVF, flow estimates based on PWD are hampered by the complex flow patterns. Overall, flow estimation based on centerline measurement, analyzed by mean-tracking of the RF-spectral estimates, under the assumption of a parabolic flow profile, appeared to provide the most reasonable values.